Automating the Indian transportation system through intelligent searching and retrieving with Amazon Elastic Compute Cloud. Issue 3 (8th April 2021) - Yadav, Siddharth; Yadav, Dileep Kumar; Budati, Anil Kumar; Kumar, Manoj; Suri, Ajay
Abstract: This article focusses on the problems associated with or unavailability of service in the Indian transportation system. Nowadays, web portal pages and Internet require most frequent search capability. In applying queries for data searches, this work procedure expressly demonstrates intriguing aspects of the query that utilize gathering terms. These gatherings are semantically correlated but separate from search results. The query is fired for the best travel route to make the travel system more intelligent. Such gatherings can be applied to real‐time applications such as those for airlines, trains, buses, and diverse and distinct flight travel classes to determine the lowest cost and shortest route. In this work, the gatherings are called query aspects. This work investigates a method for web applications that searches for data from a user search and generates a list of the shortest and lowest cost travel routes. A proposed intelligent algorithm is developed and analysed for searching data effectively. The user selects from a list of the low‐cost, shortest routes by the preferred mode of travel (flight/train/bus). The proposed method reduces customer dependency on solely vehicle (cab/bus/train) services, where prices may be too high and travel time too long. The proposed method demonstrates suitable performance by visualization of data against considered peer methods.